Facile Synthesis of Hollow MgO Spheres and Their Fluoride Adsorption Properties - Yong Zhang; Zhen Jin; Liao Min-He; Xu Guang-Song; Xu Min-Da; Hui Cheng; Jian Huang (Advances in Condensed Matter Physics)
In the present work, the hollow MgO spheres were synthesized through a facile wet-chemistry method. X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and energy dispersive spectrum are employed to characterize the as-prepared sample. Those results indicate that the average size of the as-prepared MgO hollow spheres is about 2 μm. Also, the MgO hollow spheres have the polycrystalline and porous structure, which would provide large specific surface area and plenty active sites for fluoride adsorption. The adsorption properties of the MgO hollow spheres towards fluoride are investigated. The fluoride adsorption kinetics of the MgO hollow spheres fits well the pseudo-second-order model. Also, the kinetic data revealed that the fluoride adsorption was rapid, more than 83% of fluoride could be removed within 40 min. The fluoride adsorption capacity of the hollow MgO spheres is larger than 182.4 mg/g at a pH of 7.0. The as-prepared products maintain excellent adsorption performance in the pH range of 3–11. In addition, the adsorption mechanism also has been discussed. From the FTIR results, a hydroxyl and carbonate coexchange mechanism is proposed. It is believed that the hollow MgO spheres are a potential candidate for fluoride removal.